Exploring microplastic impact on whole blood clotting dynamics utilizing thromboelastography - Christodoulides, Alexei; Hall, Abigail; Alves, Nathan J. (Frontiers in Public Health, 2023)
This study investigates the influence of microplastics on blood clotting. It addresses the lack of comprehensive research on the effects of microplastic size and surface modification on clotting dynamics in human whole blood. Thromboelastography was used to examine aminated (aPS), carboxylated (cPS), and non-functionalized (nPS) polystyrene particles with sizes of 50, 100, and 500 nm. Results show that cPS consistently activated the clotting cascade, demonstrating increased fibrin polymerization rates, and enhanced clot strength in a size and concentration-dependent manner. nPS had minimal effects on clotting dynamics except for 50 nm particles at the lowest concentration. The clotting effects of aPS (100 nm particles) resembled those of cPS but were diminished in the 500 nm aPS group. These findings emphasize the importance of microplastic surface modification, size, concentration, and surface area on in-vitro whole blood clotting dynamics.